Onset of southwesterly wind over eastern China and associated atmospheric circulation and rainfall - Zhao, Ping; Zhang, Renhe; Liu, Jiping; Zhou, Xiuji; He, Jinhai (Climate dynamics, 2007)
Using the 5-day averaged data from the National Center for Environmental Prediction/National Center for Atmospheric Research (NCEP/NCAR) reanalysis, and precipitation from rain gauge stations in China for the period 1981-2000, we investigated seasonal variations and associated atmospheric circulation and precipitation of the southwesterly wind over eastern China. The southwesterly wind over eastern China begins earliest over southeastern China and strengthens gradually from spring to the early summer, as it extends northward. The strengthening of the spring southwesterly wind, the tropospheric upward motion, and the convergence of low-level water vapor over southeastern China results in the beginning of the local rainy season. The beginning of the Mei-yu (Plum rainfall) is connected with the northward march of the southwesterly wind. The southwesterly wind reaches the valley of the Yangtze River in the early summer and northern China in the middle summer. This signifies an onset of the large-scale southwesterly wind over eastern China. Accordingly, the rain belt over southeastern China moves to the valley of the Yangtze River in the early summer and to northern China in the middle summer. Moreover, the southerly wind extends southward to the South China Sea from the spring to summer, though it does not stretch from the South China Sea to southeastern China at those times. The strengthening of the southerly wind over southeastern China is associated with a weakening/strengthening of the eastward/westward subtropical tropospheric temperature gradient between southwestern China and the western North Pacific. The developments of a low-pressure system over southwestern China and the subtropical high-pressure system over the western North Pacific may contribute to the strengthening of the southwesterly wind. A northward advance of the high-pressure system favors the southwesterly wind stretching from southeastern China to northern China. The onset of the Indian summer monsoon also strengthens the summer southwesterly wind over eastern China.